2020
DOI: 10.32793/jida.v3i1.449
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Acidity, Salivary Flow Rate and Caries Index in Electronic Cigarette Users in Sleman Regency, Indonesia

Abstract: Introduction: The Yogyakarta Special Region ranks sixth for highest number of smokers of the 33 provinces in Indonesia. Smokers account for 31.6% of the total population. Sleman Regency ranks fourth in daily consumption of cigarettes of the five regencies or cities in Yogyakarta. The body part most exposed to direct cigarette smoke is the oral cavity. Saliva is a liquid secreted inside the oral cavity to act as a buffer. Nicotine content in conventional cigarettes is known to diminish the salivary flow rate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…To enhance the avor and smell, e-cigarette liquids usually contain sucrose, sucralose, and sugar alcohol as additions (33) (34). While the current research was not in accordance with Lestari et al's (2020) ndings, which suggested that the caries index of smokers who use e-cigarettes is similar to that of non-smokers (35).…”
Section: Discussioncontrasting
confidence: 84%
“…To enhance the avor and smell, e-cigarette liquids usually contain sucrose, sucralose, and sugar alcohol as additions (33) (34). While the current research was not in accordance with Lestari et al's (2020) ndings, which suggested that the caries index of smokers who use e-cigarettes is similar to that of non-smokers (35).…”
Section: Discussioncontrasting
confidence: 84%
“…Lestari et al investigated the direct effect of smoking ECs on SFR and the salivary pH, and their results clearly indicated a significantly lower pH in EC smokers as compared to non-smokers, but no significant difference in the SFR levels between the 2 groups. 150 However, the methodology of their experiment did not include the collection of saliva from traditional cigarette smokers and the comparison of the traditional smokers with the vaping group. 150 This relationship was taken into account by Mokeem et al, whose results did not reveal any changes in the SFR values between the 3 study groups (EC smokers vs. traditional smokers vs. non-smokers).…”
Section: Effect Of Smoking Electronic Cigarettes On the Salivary Secr...mentioning
confidence: 99%
“…150 However, the methodology of their experiment did not include the collection of saliva from traditional cigarette smokers and the comparison of the traditional smokers with the vaping group. 150 This relationship was taken into account by Mokeem et al, whose results did not reveal any changes in the SFR values between the 3 study groups (EC smokers vs. traditional smokers vs. non-smokers). 145 In research performed by Cichońska et al, pH was lower, and total protein, Ca and phosphate concentrations were higher in EC users in than non-smokers.…”
Section: Effect Of Smoking Electronic Cigarettes On the Salivary Secr...mentioning
confidence: 99%